Finite-Time Vibration-Attenuation Controller Design for Structural Systems with Parameter Uncertainties. (3rd April 2014) - Ding, Yuanchun; Weng, Falu; Ge, Ji; Liang, Liming; Yang, Guoliang
Abstract : The problem of finite-time vibration-attenuation controller design for buildings structural systems with parameter uncertainties is the concern of this paper. The objective of designing controllers is to guarantee the finite-time stability of closed-loop systems with a prescribed level of disturbance attenuation. First, based on matrix transformation, the structural system is described as state-space model, which contains parameter uncertainties. Then, based on finite-time stability analysis method, some sufficient conditions for the existence of finite-time vibration-attenuation controllers are obtained. By solving these conditions, the desired controllers can be obtained for the closed-loop system to be finite-time stable with the performance ∥ z ∥ 2 < γ ∥ ω ∥ 2 . It is shown by the simulation results, that compared with some Lyapunov asymptotic stability results, finite-time stability control can obtain better state responses, especially while the system is under nonzero initial states.